QALSIC: building an articulate educational software for high school inorganic chemistry laboratories - Mustapha, S.S.; Zain, Sharifuddin Md; Pang, J.S. (2005)
In building an intelligent tutoring system, researchers quest for robust techniques and suitable approaches so that intelligent and interactive communications between learners and the system can be seamlessly established. The aspects of communication encompass the four properties of articulate software defined by Forbus (2001) which are fluent, supportive, generative and customizable. The building of articulate software (QALSIC) for learning inorganic chemistry at high school level is discussed in this paper. The four properties are represented in our system through knowledge-based and qualitative process theory approaches. The interactiveness and intelligence of the system are demonstrated in its intelligent responses to unprecedented events, unknown substances, and flexibility in usage. The system can be used symbiotically with the traditional laboratory, as well as, as an independent system in which it offers a more flexible learning environment at a lower cost. The strength of the system is centred at its explanatory capabilities in using chemistry knowledge. We envisage that the system will improve intuitive learning in students while enhancing the traditional didactic learning.